Maternal exposure to PM2.5 induces the testicular cell apoptosis in offspring triggered by the UPR-mediated JNK pathway. Issue 1 (26th January 2022) - Ren, Lihua; Jiang, Jianjun; Huang, Jing; Zang, Yu; Huang, Qifang; Zhang, Lianshuang; Wei, Jialiu; Lu, Hong; Wu, Shaowei; Zhou, Xianqing
Abstract: Contemporary exposure to PM2.5 has been reported to disrupt spermatogenesis. However, the subsequent toxicological responses and the mechanisms of male reproductive damage in offspring induced by maternal exposure to PM2.5 remain largely unknown. For the first time, this study aimed to explore the apoptotic response in spermatogenesis of male offspring following maternal exposure to PM2.5 and its mechanisms. The C57BL/6 mice with vaginal plugs were randomly divided into four groups. Mice in the PM2.5 groups were intratracheally exposed to PM2.5 (4.8 mg/kg body weight, 43.2 mg/kg body weight) during pregnancy (every 3 days, six times in total). The mice in the membrane control group were treated similarly to the PM2.5 groups, applying only PM2.5 sampling membrane, while mice in the control group were kept untreated. The results showed that maternal exposure to PM2.5 during pregnancy resulted in structural lesions of the testis, reduced numbers of primary spermatocytes and spermatids, decreased sperm count and quality, shortened diameter of seminiferous tubules, and reduced testosterone and ABP in the offspring testes. Furthermore, cell apoptosis was increased and protein expression of IRE-1/P-JNK/cleaved caspase-12/cleaved caspase-3 was activated. These findings suggested that maternal exposure to PM2.5 may affect spermatogenesis by increasing apoptosis through activation of UPR-mediated JNK apoptotic pathway in offspring testicles and by reducing testosterone secretion.